Downdraft rice husk furnace for paddy drying adopted in Southeast Asia - CGIAR Research Program on Rice (2019)
The downdraft rice husk furnace for paddy drying was developed by IRRI in collaboration with the University of Hohenheim and Nong Lam University. The technology was transferred to the private companies in the Philippines, Indonesia, Vietnam, Myanmar, and Cambodia. As of June 2019, about 200 and 40 units in the Philippines and Indonesia, respectively.